2013
DOI: 10.1159/000351933
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Skin Barrier from Down Under

Abstract: Over the past 40 years the Australian contribution to the field of skin science has been led by Michael Roberts. One of his earliest papers on membrane permeation was published in Nature, setting the scene for his huge contribution to both the fundamental understanding of skin permeability and the application of that knowledge to improved clinical outcomes, new delivery technologies and minimizing toxicological risk. His work has been characterized by a mechanistic, mathematical approach to defining skin perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…The barrier function of the skin is mostly provided by the lipids of the stratum corneum [1,2,3,4]. External stressors are able to influence the physiology of the human skin's stratum corneum.…”
Section: Introductionmentioning
confidence: 99%
“…The barrier function of the skin is mostly provided by the lipids of the stratum corneum [1,2,3,4]. External stressors are able to influence the physiology of the human skin's stratum corneum.…”
Section: Introductionmentioning
confidence: 99%
“…Kanda and Watanabe [19 ]demonstrated that estradiol suppresses apoptosis in keratinocytes by promoting Bcl-2 expression and induces the expression of cyclin D2, an important cell-cycle regulatory protein [20]. Estrogen may also play a role in the stratum corneum barrier function [21,22,23,24]. …”
Section: Discussionmentioning
confidence: 99%